Por uma pedagogia crioula : memória, identidade e resistência no quilombo de Conceição das Crioulas – PE - Nascimento, Márcia Jucilene do (Universidade de Brasília, 2017)
This dissertation aims to describe the specific schooling process developed in the quilombo of Conceição das Crioulas, in Salgueiro / PE. This process was a result of the socio-historical reconstruction movement of the quilombo’s history, which started in the 1980s. This process triggered several conflicts, and priority was given to the regaining of their territory and to the search for educational practices with decolonizing ideals. Based on the individual and collective memories of Conceição das Crioulas people, we have registered the historical accounts of the community’s resistance to the domination and oppression systems imposed to them since the arrival of the creole founders until today. The methodological trajectory was based on interviews, informal conversations and the analysis of a video-documentary, specifically recorded for this research. This path also allowed us to evaluate how we have perceived and done our school education over a period of twenty-two years, whose milestone is the inauguration, in 1995, of Professor José Mendes school, a local public school where grades 6th to 9th are taught. First, this paper addresses important elements for the beginning of this search. Next, it describes practices and specific actions of the education of Conceição das Crioulas. After that, it draws a comparative analysis about this and other pedagogical experiences, highlighting connections and significant distances between them. Finally, at the end of the last chapter, it conceptualizes this experience, which was named Crioula Pedagogy in the community.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; _À analyser